The use of mud in Portugal: past and present - Teixeira, Frederico (Anales de Hidrología Médica, 2012)
Peloid are "products formed by spontaneous or artificial mixture of natural mineral water, sea water or salt lake, with a solid component (organic or inorganic), resulting from biological or geological processes (or both) in the natural state or after preparation, are used topically for therapeutic purposes in the form of poultices or baths "(VI Conf. Int Soc Med Hydr., 1949). Thus considered, the peloid in the natural state or after preparation (ripening) have therapeutic interest for the use of its thermal effect, nonspecific, but they also will be important to consider their specific effect dependent on their physical and chemical composition (silica, Biogel existing or developed during the maturation process, and the consequent enrichment sulfurárea ion, formation of reducing or oxidizing substances, humic acids and other compounds of steroid structure, etc.).. In this specific effect is important to consider the effect scaly (silica and sulfur), buffering (colloidal silica), antiseptic (sulfur), anti-inflammatory (resolving power, chlorinated waters; action of humic acids and other steroid structure, sulphurous waters). In Portugal, and for many years, were used: a) natural peloids - of the Cucos Spa, Torres Vedras (hipertonic waters, sodium chloride, silica) and the Azores, among others in the Thermal Furnas (hipertonic water, sulphurous, and alumina silicate, some ferruginous). b) artificial peloids - made from sludge deposits collected from the bed of the Vouga river, near Aveiro, and properly cleaned and prepared for further maturation in tanks fed the sulphurous water 37-39° C for 6 months, so to acquire a very high amount of sulfurárea, a practice used for years in Vizela and Aregos spas. c) Each other and were later used in the treatment of rheumatic diseases and other musculoskeletal disorders or therapy eczematous dermatoses (eg psoriasis). d) In the early 90s of last century, everything changed: First, the closure of of Cucos spas (who are awaiting restoration), then under the law but produced and which increased the accuracy of microbiological control the use of mineral water at the spa, or by simultaneous economistic strategy, Vizela and Aregos spas stopped growing artificial maturation of peloid. In its place, began to use something they call "muds", sometimes mixed with paraffin ("muds") and are nothing more than "extemporaneous preparations" of any product purchased elsewhere abroad loamy, mixed on thermal water and put the heat to high temperature in a "pot of stainless steel" (which, as a rule, receive more pompous other names). In most cases, the application of such "products" will be completed in poultices hot (40-45° C) that most do not act other than as "moist heat" nonspecific and, as such, the Portuguese law of 2004, should not be considered "thermal techniques" but only "complementary techniques," since they can not be recognized Crenotherapy effect. Such practice, however and unfortunately, has become widespread in many of the spas in Portugal, in abusive use of the name of "muds" which, in our view, does nothing to dignify hydrotherapy. Across the thalassotherapy, Portugal has some areas with "marine mud," natural and some quality, some enriched with various types of algae that naturally mature in these deposits, such as the beach of Foz do Minho, Consolation Beach (Peniche) Praia do Meco (Caparica) and some of the Algarve coast. Unfortunately, such "marine mud" have only been exploited by people spontaneously, without any organized therapeutic environment. Is it time to produce adequate legislation for the SPA, similar to what exists for Thermal Therapy, and from there develop a correct therapeutic use of marine mud.
Keywords: Mud; Peloid; Portugal